2011
DOI: 10.1103/physrevb.84.115407
|View full text |Cite
|
Sign up to set email alerts
|

Surface energy and excess charge in (1×2)-reconstructed rutile TiO2(110) from DFT+U

Abstract: Physically reasonable electronic structures of reconstructed rutile TiO2(110)-(1×2) surfaces were studied using density functional theory (DFT) supplemented with Hubbard U on-site Coulomb repulsion acting on the d electrons, so called as the DFT+U approach. Two leading reconstruction models proposed by Onishi-Iwasawa and Park et al. were compared in terms of their thermodynamic stabilities.PACS numbers: 71.15. Mb, 68.47.Gh Rutile TiO 2 and its surfaces represent model systems to explore the properties of tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(59 reference statements)
0
11
2
Order By: Relevance
“…Very recently, López et al 19 paid particular attention to the study of the electronic structures of the TiO 2 (110)-(1 Â 2) surface and identified for the first time an asymmetric feature of the band gap states (BGSs) due to the mixed contributions among bulk defects and surface Ti 2 O 3 -terminations. 20,21 These calculation results are not in agreement with the reduced dispersion experimentally observed by angle resolved photoelectron spectroscopy experiments for the gap states of the (1 Â 2) surface. 20,21 These calculation results are not in agreement with the reduced dispersion experimentally observed by angle resolved photoelectron spectroscopy experiments for the gap states of the (1 Â 2) surface.…”
Section: Introductioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Very recently, López et al 19 paid particular attention to the study of the electronic structures of the TiO 2 (110)-(1 Â 2) surface and identified for the first time an asymmetric feature of the band gap states (BGSs) due to the mixed contributions among bulk defects and surface Ti 2 O 3 -terminations. 20,21 These calculation results are not in agreement with the reduced dispersion experimentally observed by angle resolved photoelectron spectroscopy experiments for the gap states of the (1 Â 2) surface. 20,21 These calculation results are not in agreement with the reduced dispersion experimentally observed by angle resolved photoelectron spectroscopy experiments for the gap states of the (1 Â 2) surface.…”
Section: Introductioncontrasting
confidence: 70%
“…It has been reported that TPA molecules in a bulk phase start to sublimate at B380 K, 49 while benzoate species chemically adsorbed on TiO 2 decompose above 650 K. 50 In addition, the two neighboring surface hydroxyl groups on the TiO 2 recombine to produce water at B490 K with simultaneous regeneration of an oxygen vacancy. Unal et al 21 calculated the surface energy and the excess charge of the (1 Â 2)-reconstructed TiO 2 (110) surface using the (DFT+U) approach. The curve (i) in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy has been associated to the tendency of the GGA functional [30] to overestimate the delocalization of states that may be otherwise localized by different factors, like correlation effects and the quasi-1D character of states running along the reconstruction chains. Indeed, the use of GGA+U as an alternative exchange and correlation functional favors the opening of a gap along the [001] direction and results in a dispersive state in the band gap, localized at the subsurface Ti atoms in the trenches between the Ti 2 O 3chains[31,32].Figure 3shows the computed valence band electronic structure for a slab (left) and the corresponding projection of bulk states along the GΓ-Z direction (right). Blue dots label states with more than an 80% contribution from atoms of the Ti 2 O 3 chains, while green dots represent the same for atoms located on the TiO 2 tri-layer closest to the surface.…”
mentioning
confidence: 99%
“…55 Ünal et al proposed that the Ti 2 O 3 structure is more stable than the Ti 2 O structure on the basis of DFT+U calculations. 56 The Ti 2 O 3 added row appears as bright stripes along the [001] direction, as shown in Fig. 1b.…”
Section: Resultsmentioning
confidence: 92%